Diversities of phthalate esters in suburban agricultural soils and wasteland soil appeared with urbanization in China - Kong, Shaofei; Ji, Yaqin; Liu, Lingling; Chen, Li; Zhao, Xueyan; Wang, Jiajun; Bai, Zhipeng; Sun, Zengrong (Environmental pollution (1987), 2012)
The distribution of six priority phthalic acid esters (PAEs) in suburban farmland, vegetable, orchard and wasteland soils of Tianjin were obtained with gas chromatography-mass spectrometer analysis in 2009. Results showed that total PAEs varied from 0.05 to 10.4 μg g−1, with the median value as 0.32 μg g−1. Di-(2-ethylhexyl) phthalate and di-n-butyl phthalate are most abundant species. PAEs concentrations for the four types of soils exhibited decreasing order as vegetable soil > wasteland soil > farmland soil > orchard soil. PAEs exhibited elevated levels in more developed regions when compared with other studies. The agricultural plastic film could elevate the PAEs contents in soils. Principal component analysis indicated the emission from cosmetics and personal care products and plasticizers were important sources for PAEs in suburban soils in Tianjin. The higher PAEs contents in wasteland soils from suburban area should be paid more attention owing to large amounts of solid wastes appeared with the ongoing urbanization. ► PAEs levels in four types of soils in suburban area of Tianjin were studied. ► Vegetable soil and wasteland soil exhibited higher PAEs concentrations. ► PAEs in wasteland soils from suburban area of cities in China should be paid attention. (1) Vegetable soil and wasteland soil exhibited higher PAEs concentrations; (2) PAEs in wasteland soils from suburban area of cities in China should be paid attention.